Efficacy of anti-thymocyte globulin for platelet transfusion refractoriness in serious aplastic anemia patients. (June 2022) - Gao, Mengying; Huang, Jinbo; Shao, Yingqi; Ge, Meili; Li, Xingxin; Zhang, Jing; Wang, Min; Nie, Neng; Jin, Peng; Zheng, Yizhou
Abstract: Platelet transfusion refractoriness (PTR) is a life threatening, intractable clinical issue suffered by some serious aplastic anemia (SAA) patients. Unlike immune thrombocytopenia, effective treatments for PTR remain largely unknown. In our clinical work, we noted that PTR in some SAA patients could be rapidly relieved with the application of anti-thymocyte globulin (ATG), therefore, we retrospectively analyzed its management and outcomes for PTR in SAA patients. A cohort including 29 SAA with PTR patients who received ATG administration was enrolled in this study. All patients suffered from PTR before ATG administration. Among the 29 PTR patients treated with ATG, 21 (72.4.0 %) patients had response, importantly, 13 (44.8 %) patients had an immediately response following the first dose of ATG administration. Bleeding events of grade 3 or above occurred in 23 patients (79.3 %). With the recovery of effective platelet transfusion, the bleeding events in responders could be quickly relieved. The non-responders suffered from aggravated bleeding, including intracranial bleeding in two non-responders, which appeared on eighth and 29th days after ATG administration. Our study indicated that ATG was an effective and safe intervention in the management of PTR in SAA patients.